Clinical trial designs for rare diseases: Studies developed and discussed by the International Rare Cancers Initiative. Issue 3 (February 2015) - Bogaerts, Jan; Sydes, Matthew R.; Keat, Nicola; McConnell, Andrea; Benson, Al; Ho, Alan; Roth, Arnaud; Fortpied, Catherine; Eng, Cathy; Peckitt, Clare; Coens, Corneel; Pettaway, Curtis; et al.
Abstract Background The past three decades have seen rapid improvements in the diagnosis and treatment of most cancers and the most important contributor has been research. Progress in rare cancers has been slower, not least because of the challenges of undertaking research. Settings The International Rare Cancers Initiative (IRCI) is a partnership which aims to stimulate and facilitate the development of international clinical trials for patients with rare cancers. It is focused on interventional – usually randomised – clinical trials with the clear goal of improving outcomes for patients. The key challenges are organisational and methodological. A multi-disciplinary workshop to review the methods used in ICRI portfolio trials was held in Amsterdam in September 2013. Other as-yet unrealised methods were also discussed. Results The IRCI trials are each presented to exemplify possible approaches to designing credible trials in rare cancers. Researchers may consider these for use in future trials and understand the choices made for each design. Interpretation Trials can be designed using a wide array of possibilities. There is no 'one size fits all' solution. In order to make progress in the rare diseases, decisions to change practice will have to be based on less direct evidence from clinical trials than in more common diseases.